Life as an information expert / Anis Syamimi Mohamad and Ain Syafika Shah Dahli - Mohamad, Anis Syamimi; Shah Dahli, Ain Syafika (Faculty of Information Management, 2015)
As information deliver becomes more important and complex, the professionals providing the services and also the way to becoming an information expert. As the information deliver, we must look into the best means accessible to us to systematize their skills and services as a mean to success the goals. Information expert can have their own purposes and benefits, also their own challenges to face with. Expert system develop in a variety of subject areas as a mean of working towards this goal to succeed as an information expert.